Fluconazole Nanosuspension Enhances In Vitro Antifungal Activity against Resistant Strains of Candida albicans - Katayoun Morteza-Semnani; Majid Saeedi; Jafar Akbari; Maryam Moazeni; Houman Seraj; Elham Daftarifard; Mahgol Tajbakhsh; Seyyed Mohammad Hassan Hashemi; Amirhossein Babaei (Tabriz University of Medical Sciences, 2022)
Background: Recently, nanoparticles were widely used in drug delivery. Fluconazole (FLZ) is a lipid-soluble antifungal, which is utilized in treating fungal infections. The current work aimed to investigate the characteristics and antifungal activity of FLZ nanosuspension. Methods: FLZ nanosuspensions were prepared by Ultrasonication (simple and containing polymer). Surfactants in various concentrations were dissolved in the deionized water, and the drug powder was dispersed in the surfactant solution by a high-speed homogenizer to achieve nanosuspension. The polymer was added to the selected formula. FLZ nanosuspension characteristics, including polydispersity, mean particle size, entrapment efficacy, and zeta potential, were assessed. The release profile via dialysis membrane, differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (ATR-FTIR), and TEM were performed for nanosuspension evaluation. Antifungal activity against resistant strains of C. albicans was defined according to the CLSI document guideline. To analyze the results, one-way ANOVA was used, followed by Tukey test. Results: The results showed that increased sonication time and hydrophilic-lipophilic balance (HLB) significantly affected particle size reduction. Moreover, modification in the formulation components had a significant effect on the drug release process, furthermore affecting the properties of the nanoparticles. ATR-FTIR showed no chemical interaction between FLZ and formulation components. Compare to FLZ, a significant reduction (p < 0.05) was detected in the MIC values of both FLZ-resistant and FLZ-susceptible strains of C. albicans against FLZ nanosuspension. Conclusion: It can be concluded that the ratio and amount of surfactants, the HLB, and the sonication process have effects on the properties of the nanoparticle's characteristics, and selected nanoparticles show suitable antifungal effect against resistant strains of C. albicans.